PEDAGOGICAL STRATEGY INQUIRY-BASED LEARNING (IBL) FOR DEVELOPMENT OF SCHOOLCHILDREN MATHEMATICAL THINKING - Astafieva Маriia; Hruzdova , Kateryna (Physical and Mathematical Education, 2022)
Formulation of the problem. Today the world is changing rapidly, the socio-economic structure of society, scientific and technological progress are quickly transforming, new challenges and threats to the economy, environment, political stability, peace, health and human life arise. These challenges require radical changes in education at all levels, including school education, so that today’s schoolchildren could successfully operate in a high-tech and dynamic society in a few years. They significantly raise the bar of requirements for mathematical training of school graduates, their creativity, ability to learn quickly and continuously, and work in a team. At the same time, the problems of mathematical training of Ukrainian schoolchildren have only deepened over the last decade. This is evidenced by the results of the annual external independent evaluation of school graduates (Ukrainskyi tsentr otsiniuvannia yakosti osvity, 2020), and disappointing indicators of mathematical literacy of Ukrainian schoolchildren in the international study PISA 2018 (Vakulenko at al, 2018). In both cases, many of them showed an inability to solve open problems, to look at problems from different angles, when it is necessary to demonstrate not formal knowledge of certain formulas or procedures, but the ability to think mathematically. Therefore, the question of changing the educational paradigm arises: moving away from such learning, when the teacher is a repeater of ready-made facts, to one in which the schoolchild is actively acquiring knowledge. Materials and methods. Theoretical (analysis of scientific sources on pedagogical strategies that promote the development of mathematical thinking, including research-oriented strategy Inquiry-based Learning (IBL)) and empirical (observation and testing of IBL tools on practice of teaching mathematics to 5th graders in one of Kyiv schools, interviews and questionnaires of schoolchildren) are used. Results. A series of mathematical tasks for 5th grade students and methodological support for their use in the process of research-oriented learning (IBL) of mathematics has been developed and tested, their influence on the formation and development of mathematical thinking of schoolchildren has been identified. Conclusions. It is established that the IBL strategy, implemented through mathematical tasks, promotes the formation and development of schoolchildren mathematical thinking.